KETERAMPILAN PEMELIHARAAN LEBAH TANPA SENGAT UNTUK PETANI KOTA - Retno Widowati; Rahayu Lestari; Adam Nurkholik; Novita Nur Rahmawati; Wdya Ningsih; Akso Diana (LPPM Universitas Bina Bangsa, 2023)
The aim of community service was provide skills in keeping stingless bees for urban farmers. The problems were the farmers need to produce more fruit crops and additional income. Stingless bees have ability to pollinate various types of flowers to produce fruit. The target of community service was group of city farmers namely Poncol Jaya, located in Ragunan area, South Jakarta. The community service took place from June to September 2023, at the Agricultural Extension Center, Ragunan, South Jakarta. The community service carried out were focus group discussions, training on introducing stingless bees and their economic potential, beekeeping training, honey harvesting training, colony split training, planting feed bee plants, and monitoring the development of stingless bees colonies. The result of community service is the urban farmers have ability to stingless beekeeping, harvesting honey and splitiing colonies, so that maintenance can be carried out sustainably